Pendamping Layanan Klampid New Generation dan Pelaksanaan Program Kalimasada di Dinas Kependudukan dan Pencatatan Sipil Kota Surabaya - Ryco Tarnuwardhana Putra; Ika Devy Pramudiana; Sri Roekminiati; Sapto Pramono; Aris Sunarya (Civiliza Publishing, 2026)
Population administration is a crucial foundation for public services. The Surabaya City Government has developed the Klampid application. New Generation (KNG) and the Kalimasada Program to improve the quality of community-based servicese-government This community service activity aims to describe the role of MSIB Batch 6 students in assisting with the use of the KNG application and the implementation of the Kalimasada Program in Ampel Village. The method used was a participatory approach through direct assistance, education, and verification of population documents. The results of the activity showed an increase in community understanding and digital literacy, accelerated document processing, and increased awareness of the importance of orderly population administration.